Chapter A New Compact VNIR Hyperspectral Imaging System for Non-Invasive Analysis in the FineArt and Architecture Fields - Picollo, Marcello (Proceedings e report, 2018)
A new compact Specim IQ hyperspectral camera working in the 400-1000 nm range has been launched on the market. Its use in the investigation of different artworks and under diverse environmental conditions will be presented.